PERSEPSI SISWA SMA MUHAMMADIYAH 1 PURBOLINGGO TERHADAP PERANAN K.H AHMAD DAHLAN DALAM PENDIDIKAN DI INDONESIA - Bagas Prakoso Wibowo; Bahtiar Afwan (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
SMA Muhammadiyah 1 Purbolinggo is a school that was established Branch of Persyarikatan Muhammadiyah Purbolinggo which in the process of learning using education renewal conducted by KH Ahmad Dahlan where general education integrates with the science of religion so that the integration in learning aims to create a young generation who excel in the field of education and spiritual In the field of religion to conform to the Qur'an and As Sunnah. Problems discussed in this study is how the perception of students of SMA Muhammadiyah 1 Purbolinggo on the role of K.H Ahmad Dahlan in education in Indonesia. The purpose of this research is (1) to know the perception of SMA Muhammadiyah 1 Purbolinggo students on the role of K.H Ahmad Dahlan in education in Indonesia, (2) to know the students' view of K.H Ahmad Dahlan. This research uses qualitative method by taking location in SMA Muhammadiyah 1 Purbolinggo, informant in this research is student of SMA Muhammadiyah 1 Purbolinggo, in technique of collecting data using observation, interview, questionnaire, method of library, document. In analyzing data using data reduction, data presentation, and conclusion. The result of this research are (1) SMA Muhammadiyah 1 Purbolinggo students still do not understand or know the renewal done by K.H Ahmad Dahlan, (2) the obstacles of student in knowing K.H Ahmad Dahlan renewal lack of learning resources and facilities and infrastructure related to K.H Ahmad Dahlan.